Alkaloids of Aconitum nasutum Fisch. ex Reichb. - Altintas, Ayhan; Kirimer, Nese; Salimov, Bahadir; Husnu Can Baser, Kemal (Asian Journal of Chemistry, 2010)
Alkaloid extracts from aerial parts and roots of Aconitum nasutum were investigated by mass spectrometry using metastable defocusing system. Two alkaloids (talatisamine and 14-acetyltalatisamine) were isolated by column chromatography. Talatisamine was found to be the major compound both in the aerial parts and the roots of the plant.